Perancangan Sistem Informasi Sederhana Pengelolaan Network Terminal Equipment (NTE) untuk Meminimasi Waktu Proses dengan Metode Waterfall pada PT. XYZ - Trisandhiya, Widhi; Nashir Ardiansyah, Muhammad; Deni Akbar, Mohammad (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
PT XYZ is a company engaged in information and communication technology services, as well as telecommunications networks in Indonesia. One of the activities carried out by PT.XYZ is the management of NTE devices, namely devices owned by PT.XYZ or partners consisting of modems, Optical Network Terminals (ONT) and Set Top Boxes (STB). In carrying out the NTE device management process, PT. XYZ, especially the digital broadband planning (DBP) unit which has the function to plan the development of access infrastructure, experiences obstacles in managing NTE device data requirements, namely the process time for managing NTE data requirements that exceed the target, the company targets the management of these data requirements for half a working day or 4-6 hours but in actual conditions the data management takes two working days. Therefore, a simple information system based on google spreadsheets was created which aims to minimize process time and eliminate unnecessary activities. The final result of this research is a cycle time cut of 238 minutes. The cycle time cut occurs because of a simple information system using google spreadsheets. This was done because before the information system, the process of inputting and processing data was done manually using Ms.Excel and required a fairly long pre-processing data.